2014
DOI: 10.1371/journal.pone.0099256
|View full text |Cite
|
Sign up to set email alerts
|

Standardising the Lactulose Mannitol Test of Gut Permeability to Minimise Error and Promote Comparability

Abstract: BackgroundLactulose mannitol ratio tests are clinically useful for assessing disorders characterised by changes in gut permeability and for assessing mixing in the intestinal lumen. Variations between currently used test protocols preclude meaningful comparisons between studies. We determined the optimal sampling period and related this to intestinal residence.MethodsHalf-hourly lactulose and mannitol urinary excretions were determined over 6 hours in 40 healthy female volunteers after administration of either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 56 publications
0
103
3
Order By: Relevance
“…Based on a prior report [16], LMR was determined using 4-h pooled urine collected from subjects who had fasted for at least 12 h, emptied their bladder, and had orally consumed a sugar solution prepared by dissolving 10 g of lactulose and 5 g of mannitol in 400 mL of water. During the fasting period, subjects were allowed to drink sugar-free water.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a prior report [16], LMR was determined using 4-h pooled urine collected from subjects who had fasted for at least 12 h, emptied their bladder, and had orally consumed a sugar solution prepared by dissolving 10 g of lactulose and 5 g of mannitol in 400 mL of water. During the fasting period, subjects were allowed to drink sugar-free water.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there are no standardized protocols, resulting in variations across studies that make comparisons difficult. As several recent studies have suggested, consistency in the probes used, test duration, and fasting times could help reduce variations . Reducing some confounding factors, as in the paper by Grover et al ., provide promising improvements to in vivo techniques …”
Section: What Do Intestinal Permeability Tests Measure?mentioning
confidence: 99%
“…Studies of TBI patients show an increase in the ratio of orally ingested lactulose (a marker of paracellular permeability) to mannitol (a marker of transcellular permeability) in urine. 16,17 The lactulose-mannitol test as well as a dye permeability test also shows that injury inflicted exclusively to the brain of rodents by methods such as controlled cortical impact (CCI) is sufficient to increase paracellular permeability. [18][19][20] Furthermore, disruption of the intestinal epithelial barrier following TBI in rodents is accompanied by decreased expression of tight junction proteins Occludin and ZO-1 as well increased expression of MLCK in the intestine, providing additional support for a paracellular mechanism.…”
Section: Tbi Increases Intestinal Permeability In Mammalsmentioning
confidence: 99%